Layer‐by‐layer nanoparticles for novel delivery of cisplatin and PARP inhibitors for platinum‐based drug resistance therapy in ovarian cancer. Issue 2 (14th June 2019) - Mensah, Lawrence B.; Morton, Stephen W.; Li, Jiahe; Xiao, Haihua; Quadir, Mohiuddin A.; Elias, Kevin M.; Penn, Emily; Richson, Aysen K.; Ghoroghchian, Paiman Peter; Liu, Joyce; Hammond, Paula T.
Abstract: Advanced staged high‐grade serous ovarian cancer (HGSOC) is the leading cause of gynecological cancer death in the developed world, with 5‐year survival rates of only 25–30% due to late‐stage diagnosis and the shortcomings of platinum‐based therapies. A Phase I clinical trial of a combination of free cisplatin and poly(ADP‐ribose) polymerase inhibitors (PARPis) showed therapeutic benefit for HGSOC. In this study, we address the challenge of resistance to platinum‐based therapy by developing a targeted delivery approach. Novel electrostatic layer‐by‐layer (LbL) liposomal nanoparticles (NPs) with a terminal hyaluronic acid layer that facilitates CD44 receptor targeting are designed for selective targeting of HGSOC cells; the liposomes can be formulated to contain both cisplatin and the PARPi drug within the liposomal core and bilayer. The therapeutic effectiveness of LbL NP‐encapsulated cisplatin and PARPi alone and in combination was compared with the corresponding free drugs in luciferase and CD44‐expressing OVCAR8 orthotopic xenografts in female nude mice. The NPs exhibited prolonged blood circulation half‐life, mechanistic staged drug release and targeted codelivery of the therapeutic agents to HGSOC cells. Moreover, compared to the free drugs, the NPs resulted in significantly reduced tumor metastasis, extended survival, and moderated systemic toxicity.